2000
DOI: 10.1076/1380-3395(200006)22:3;1-v;ft391
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Age-Related Decline on the Reading Span Task

Abstract: We examined the effect of age on working memory with a reading span task (RST) together with other verbal span tasks. Sixty-two participants were divided into three subgroups (young, middle-aged, and elderly). The RST performances were significantly different among all the subgroups. To elucidate which component of the working memory system is affected by age, we performed an analysis of covariance with the scores of simple and complex verbal span tasks as covariates. From the results, we conclude that the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
1
11
0
3
Order By: Relevance
“…More recently, evidence has supported the claim that central executive functions, rather than storage capacity, are affected in aging (Van der Linden, Bredart, & Beerten, 1994). However, other studies have concluded that there are age-related declines in the capacity of the phonological loop (Meguro et al, 2000). Some investigators have argued that the capacities of both the phonological loop and the central executive are preserved with aging but that a general slowdown in perceptual speed explains the changes in performance (Fisk & Warr, 1996;Salthouse, 1985).…”
Section: Effects Of Normal Agingmentioning
confidence: 99%
“…More recently, evidence has supported the claim that central executive functions, rather than storage capacity, are affected in aging (Van der Linden, Bredart, & Beerten, 1994). However, other studies have concluded that there are age-related declines in the capacity of the phonological loop (Meguro et al, 2000). Some investigators have argued that the capacities of both the phonological loop and the central executive are preserved with aging but that a general slowdown in perceptual speed explains the changes in performance (Fisk & Warr, 1996;Salthouse, 1985).…”
Section: Effects Of Normal Agingmentioning
confidence: 99%
“…More recently, evidence has supported the claim that central executive functions, rather than storage capacity, are affected in aging ( Van der Linden, Bredart, & Beerten, 1994). However, other studies have concluded that there are age-related declines in the capacity of the phonological loop (Meguro et al, 2000). Some investigators have argued that the capacities of both the phonologicalloop and the central executive are preserved with aging but that a general slowdown in perceptual speed explains the changes in performance (Fisk & Warr, 1996;Salthouse, 1985).…”
Section: Effects Of Normal Agingmentioning
confidence: 99%
“…Normal aging, even independently of lifestyle and health issues, entails a decline of numerous cognitive abilities, including attention (Meguro et al, 2000;Morris, Craik, & Gick, 1990;Wiens, Fuller, & Crossen, 1997;Ziegler, Rambach, Klagge, & Goldammer, 1979), planning (Godbout, Doucet, & Fiola, 2000;Hess, Donley, & Vandermass, 1989;Kliegel et al, 2000), retrospective memory (Maylor, Smith, Della-Sala, & Logie, 2002), and prospective memory (Cherry & Lecompte, 1999;Gould, McDonald-Miszczak, & King, 1997;Vogels, Dekker, Brouwer, & de Jong, 2002;West & Covell, 2001;West & Craik, 1999). Advancing normal senescence eventually compromises activities of daily living (ADLs) (DeLuca et al, 2003;Femia, Zarit, & Johansson, 1997;Willis, 1996).…”
mentioning
confidence: 97%